Helicobacter pylori Infection and Hematologic Disorders: what do We Really Know? - Bruna Maria Roesler (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
One of the most important events on gastroenterology certainly was the isolation of Helicobacter pylori (H. pylori) by Barry Marshall and Robin Warren in 1983 [1], occurrence which redirected our understanding of the pathophysiology of gastrointestinal diseases. The production of urease as well as the mobility of these bacteria promoted by flagella were identified as essential factors for colonization of the gastric epithelium and, from there, within a few years, the list of H. pylori virulence factors for colonizing and persisting on the gastric surface epithelium besides some factors damaging the mucosa expanded greatly.